2010
DOI: 10.3329/agric.v6i1.5213
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habits of the Mangrove Sesarmid Crab <i>Neosarmatium trispinosum</i> (Crustacea) in the Ryukyu Islands, Japan

Abstract: Sesarmid crabs are reported to dominate the Indo West-Pacific mangroves and consume huge amounts of mangrove leaves and detritus. Neosarmatium trispinosum Davie (1994) is common in the landward mangroves of the Ryukyu Islands in southern Japan. Stomach contents of the crabs collected from Okinawa, Miyako and Iriomote Islands showed that their diet consisted of mainly mangrove leaves with small amounts of sediments indicating that N. trispinosum is primarily detritivorous. The feeding preference of N. trispinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Mangrove leaf and crab samples were collected during the post‐monsoon season. The field‐based mangrove leaf preference experiment using sesarmid crabs displayed a distinct preference for green and yellow leaves over brown leaves (Cannicci et al., 2002; Harada & Lee, 2016), whereas laboratory experiments suggest the distinct preference for decayed leaves over yellow and green ones (Giddins et al., 1986; Islam et al., 2010; Micheli, 1993). As there exists no significant difference in the δ 15 N and δ 13 C signatures of green, yellow and brown mangrove leaves (Connolly et al., 2003), mature green leaves were selected for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Mangrove leaf and crab samples were collected during the post‐monsoon season. The field‐based mangrove leaf preference experiment using sesarmid crabs displayed a distinct preference for green and yellow leaves over brown leaves (Cannicci et al., 2002; Harada & Lee, 2016), whereas laboratory experiments suggest the distinct preference for decayed leaves over yellow and green ones (Giddins et al., 1986; Islam et al., 2010; Micheli, 1993). As there exists no significant difference in the δ 15 N and δ 13 C signatures of green, yellow and brown mangrove leaves (Connolly et al., 2003), mature green leaves were selected for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, it was found that L. politum also consumes animal materials from their natural habitats where this crab had been seen to prey on grasshopper in the mangrove of Philippines and Singapore (Ng et al, 2015). Occasionally, herbivorous sesarmid crabs tend to be shifted towards opportunistic feeder when animal materials were present (Erickson et al, 2008) and it is believed that additional nutrition can be obtained by feeding on the animal tissues (Giddins et al, 1986;Islam et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%